INFLUENCING FACTORS IN SPATIAL OPTIMIZATION OF RURAL SETTLEMENTS IN SOUTHWEST FUJIAN GUIDED BY ECOLOGICAL WISDOM - Jie , Tian; Mohd Hussain, Nur Huzeima; Hamzah, Helmi; Abdullah, Suzanah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Under the current backdrop of the simultaneous advancement of ecological civilization construction and rural revitalization, optimizing the spatial layout of rural settlements in mountainous and wetland complex areas under ecological constraints has become a particularly urgent issue that requires everyone’s attention and emphasis. This article takes the southwestern part of Fujian Province as an example to systematically review the research on ecological wisdom and the spatial evolution of rural settlements. This paper employs literature review, text analysis, and policy analysis to identify and synthesize the key factors influencing the optimization of rural settlement spatial patterns under ecological wisdom, from five dimensions: natural environment, transportation and accessibility, socio-economic conditions, historical culture, and policy governance. The research shows that the natural environment is the ecological foundation for the evolution of settlements and their disaster resistance capacity. The social and economic factors and transportation together have shaped the "mountain-valley - road-village" beaded pattern, as well as the evolutionary path where agglomeration and contraction coexist. Historical and cultural factors, through the Tulou settlements and clan networks, have maintained the continuity of the settlement forms and preserved local characteristics. Under the territorial spatial planning system and the ecological civilization agenda, policies and governance have reshaped the logic of spatial regulation and control. This research summarizes a set of influencing factors for the spatial optimization of rural settlements in mountainous wetland complex areas, providing a reference for related research and planning applications.